2003
DOI: 10.1080/713848548
|View full text |Cite
|
Sign up to set email alerts
|

Elements Influencing Cost Allocation in the Pinal Creek Aquifer, Arizona, USA. Part I: Geochemical Fingerprinting and Source Delineation

Abstract: This is the first in a three-article series in this volume of Environmental Forensics describing the framework that was developed to quantitatively allocate mass loading of metals to the Pinal Creek alluvial aquifer. This article describes geochemical fingerprinting, followed by spatial and temporal analysis of Pinal Creek monitoring well data (more than 600,000 records from hundreds of locations), which identified three distinct source areas and plumes on the basis of facility-specific differences in process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Forensic techniques described by Helgen et al (2003) identified three distinct plumes based on different ratios of Cl, Cu, and Fe that are directly attributable to the loss of mining solutions from large-scale leaching of Cu ore with ferric sulfate and/or sulfuric acid. The utility of these constituents results from their transport at close to groundwater velocities (∼0.5 m/day) in the acidic core of the plume.…”
Section: Forensic Geochemistrymentioning
confidence: 99%
“…Forensic techniques described by Helgen et al (2003) identified three distinct plumes based on different ratios of Cl, Cu, and Fe that are directly attributable to the loss of mining solutions from large-scale leaching of Cu ore with ferric sulfate and/or sulfuric acid. The utility of these constituents results from their transport at close to groundwater velocities (∼0.5 m/day) in the acidic core of the plume.…”
Section: Forensic Geochemistrymentioning
confidence: 99%